A Study of Rhymes in Pope’s Poems: A Historical Perspective - Raden Roro Rieta Anggraheni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Rhyme is a poetic device that can be studied to know the poetic style of certain writer. The rhyme which was used in historical poetry will also provide a clue of the word pronunciation in certain era in the past. This study investigates the rhymes used by Alexander Pope in the late seventeenth century (early eighteen century), an era called Modern English which is interesting for its in-between characteristics, meaning that the language is similar to and different from current English. Accordingly, this study also aims at identifying the distinctive phonological feature in the form of vowel shift and unveiling the historical background of Pope’s rhyme choice. In order to achieve the purposes, the researcher analyzed fifteen poems written by Pope. The result shows that the rhyme scheme mostly used by Pope is the couplet aabbcc, even though the pattern varies. Some of the rhyming words give a clue on the pronunciation through the vowel shifts, by comparing them to the current English. Some of the vowels were more likely the result of the Great Vowel Shift effect in Renaissance era. Historically, the type of rhyme used by Pope shows that poems, as satirical verses, were used as an ideal vehicle to criticize the situation of English language development and the authority.